Information model of intelligence and memorizing in early childhood - Vidučić, Vinko (Array, 2009)
The object of analysis of this paper is global model of intelligence and memorizing of information from conception until a child starts to walk for the period from 2009 until 2020. In order to define main characteristics and determinants, the model of growth was used. Numerous adequate scientific methods were used, the most important among them: analysis and synthesis method, inductive and deductive method, descriptive method, comparative method, statistical and mathematical method, modelling method (matrix of growth), proving and disproving method. As model variables are chosen key factors for strengthening of intelligence, and therefore of memorising of information. Quantitative analysis is than used in order to determine importance of individual variables as well as their interdependence.